Epigenetic modification of ferroptosis by non-coding RNAs in cancer drug resistance - Wang, Hongquan; Fleishman, Joshua S.; Cheng, Sihang; Wang, Weixue; Wu, Fan; Wang, Yumin; Wang, Yu (Molecular cancer, 2024)
The development of drug resistance remains a major challenge in cancer treatment. Ferroptosis, a unique type of regulated cell death, plays a pivotal role in inhibiting tumour growth, presenting new opportunities in treating chemotherapeutic resistance. Accumulating studies indicate that epigenetic modifications by non-coding RNAs (ncRNA) can determine cancer cell vulnerability to ferroptosis. In this review, we first summarize the role of chemotherapeutic resistance in cancer growth/development. Then, we summarize the core molecular mechanisms of ferroptosis, its upstream epigenetic regulation, and its downstream effects on chemotherapeutic resistance. Finally, we review recent advances in understanding how ncRNAs regulate ferroptosis and from such modulate chemotherapeutic resistance. This review aims to enhance general understanding of the ncRNA-mediated epigenetic regulatory mechanisms which modulate ferroptosis, highlighting the ncRNA-ferroptosis axis as a key druggable target in overcoming chemotherapeutic resistance.